The Price of Justice: New National and State-Level Estimates of the Judicial and Legal Costs of Crime to Taxpayers - Hunt, Priscillia (American journal of criminal justice, 2017)
Programs that prevent crime cost money. In order to efficiently allocate these limited funds, we need to know how much people benefit from crime prevention. While there are some comprehensive estimates of the cost of (or benefits of avoiding) crime to victims and to society at large, we have very limited crime-specific information on the legal system resources that would be freed up for other purposes across states. Using a Monte Carlo simulation approach to take into account uncertainty in the data, this study finds the national average costs to taxpayers for judicial/legal services per reported crime are likely around the following (in 2010 dollars): $22,000–$44,000 (homicide), $2000–$5000 (rape and sexual assault), $600–$1300 (robbery), $800–$2100 (aggravated assault), $200–$600 (burglary), $300–$600 (larceny/theft), and $200–$400 (motor vehicle theft). At a state-level, the costs of crime are 50 % to 70 % more or less than these national averages depending on the crime type and state. These estimates can be used to understand the level of resources spent per crime and the potential legal resources freed up for a change in reported crime rates; they are not a measure of waste or efficiency, but it is hoped this study contributes to this debate.